Economics of biofuels and bioproducts from an integrated pyrolysis biorefinery. (8th September 2016) - Dang, Qi; Hu, Wenhao; Rover, Marjorie; Brown, Robert C.; Wright, Mark M.
Abstract: This paper describes a novel integrated biorefinery based on fast pyrolysis and subsequent bio‐oil upgrading to produce three product portfolios: hydrocarbon biofuels (gasoline and diesel), bio‐based products (bioasphalt, calcium acetate, and dextrose), and hydrocarbon chemicals (aromatics, olefins, and fuel oil). Based on the economic assumptions and historical market prices of the products, we calculate internal rates of return (IRRs) of the biorefinery (2000 dry metric tons per day) over 30 years to evaluate its performance. Given the historical low, average, and high prices of the products, a total of 27 scenarios are explored and the maximum IRR for each scenario is determined. Results indicate that upgrading bio‐oil to bio‐based products yields the maximum IRR of 67.9% if bio‐based products can be marketed at a historical high price level (between $257 and $1491 per metric ton) and an IRR of 42.5% at an average price level (between $240 and $950 per metric ton). Under some market conditions, the biorefinery should produce hydrocarbon chemicals or biofuels to increase the IRR. We also estimate the IRR probability distribution using Monte Carlo simulation by ‐incorporating distributions of product prices and bio‐oil fractions allocated for three product portfolios. Average IRRs of −3.9% for biofuels, 42.7% for bio‐based products, and 17.3% for hydrocarbon chemicals are observed with standard deviations of 24.4%, 24.1%, and 6.5%, respectively. The integrated ‐biorefinery exhibits an IRR distribution of 16.2% ± 16.4% suggesting that the integrated biorefinery could balance the economic disadvantages and benefits from individual product portfolio to achieve profitable IRRs. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd